Factors relating to mining safety compliance and non-compliance on South African mines - Seitireng, Kamogelo (My University, 2019)
The research on mining safety compliance and non-compliance has uncovered both structural as well as agency factors contributing to compliance and non-compliance. The structural factors include bonus pressure, pressure from shift bosses as well as production pressure. The agency factors include deliberate non-compliance, complacency and interpersonal workers conflict. The sample size is 64 mineworkers, who were interviewed, largely in the training centres of the specific research sites, and thematic analysis was applied in analysing the data
A Research Report submitted in partial fulfilment of the requirements for the degree of Masters of Arts of the University of the Witwatersrand
Keywords: Mine safety--South Africa; Industrial safety